2009
DOI: 10.1123/jpah.6.4.467
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Accelerometer-Guided Physical Activity Intervention in Community-Dwelling Older Women

Abstract: Background:Although many Japanese older adults spend more than an hour each day walking for exercise, the intensity is often lower than the minimum level associated with various health benefits. The purpose of this study was to evaluate the efficacy of a lifestyle physical activity intervention on improving quantity and quality of daily physical activity (DPA) as well as cardiorespiratory endurance in community-dwelling older women.Methods:68 women (60–78 yr of age) were randomly assigned to either a lifestyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Regarding the effects of the education program on health behavior, average number of steps per day, physical activity level, and dietary variety increased significantly. Based on existing physical activity intervention research findings, in which typical behavioral change techniques (feedback, goal‐setting) were provided, participants took 7% to 54% more steps per day . In the present study, intervention group participants actively learned the importance of healthy lifestyle, and planned behavioral change independently planned behavioral change.…”
Section: Discussionmentioning
confidence: 92%
“…Regarding the effects of the education program on health behavior, average number of steps per day, physical activity level, and dietary variety increased significantly. Based on existing physical activity intervention research findings, in which typical behavioral change techniques (feedback, goal‐setting) were provided, participants took 7% to 54% more steps per day . In the present study, intervention group participants actively learned the importance of healthy lifestyle, and planned behavioral change independently planned behavioral change.…”
Section: Discussionmentioning
confidence: 92%
“…Accelerometers are particularly useful in providing objective feedback of ambulatory activity to investigators and study participants in exercise adherence research [75]. Koizumi et al [76] evaluated the efficacy of accelerometer-based feedback on daily physical activity in community-dwelling older women and found that using accelerometers can significantly improve the quantity and quality of daily physical activity as well as cardiorespiratory endurance.…”
Section: Biomechanical Biofeedbackmentioning
confidence: 99%
“…The future of motivating with accelerometers has been demonstrated by Koizumi, et al 12 Although not focused on cancer survivors specifically, their intervention allowed participants to download their accelerometer results to review for motivational purposes. This same concept supports future studies of biometric calorie management systems (e.g., bodybuggR) that combine accelerometer data with other body measurements (e.g., skin temperature, etc)(http://www.bodybugg.com/science_behind_bodybugg.php) to provide caloric expenditure information that can be downloaded by the individual.…”
Section: Resultsmentioning
confidence: 99%
“…6 Objective monitoring, however, can be less expensive (depending on the equipment used and clinical charges for testing) and is a valid tool for assessing PA in the field and motivating PA adherence. 9–12 Their dual purpose and potential for objectivity support accelerometers and pedometers as particularly useful tools for optimizing the health benefits of PA after a cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%